Pemanfaatan Kecerdasan Artifisial (Artificial Intelligence/AI) Dalam Kerangka Pancasila - Grace Juanita (Jurnal Interpretasi Hukum, 2024)
The development and advancement of technology, especially the Industrial Revolution 4.0, introduced humans to artificial intelligence (AI). AI plays a role in changing human lifestyles. There are logical and fair characters and use considerations of justice and human values, according to the Pancasila framework. This study presents the issue of whether Pancasila values are beneficial for the utilization of artificial intelligence. How is artificial intelligence utilized within the Pancasila framework? According to the issue studied, it answers that artificial intelligence, which continues to develop rapidly, has not been able to be in the corridor of its main objectives, namely the protection of human rights and respect for human dignity in the digital era. Even though the values of Pancasila are taught and grounded in the social environment, human behavior has not changed according to the targeted goals. Often the development model of artificial intelligence does not always adhere to ethical values, especially in areas that are closely related to efforts to replace the role of humans, who are vulnerable to eliminating respect for the nobility of human dignity.